Air Travel-Triggered Tension Pneumocephalus Caused by a Frontal Sinus Osteoma: Case Report - Aleksandar Djurdjevic; Milan Lepic; Jovana Djurdjevic; Svetozar Stankovic; Goran Pavlicevic (Reports)
Background and Clinical Significance: Pneumocephalus, an accumulation of air within the cranial cavity, typically arises from trauma or iatrogenic causes. However, spontaneous occurrences of this are rare and linked to various pathologies affecting the paranasal sinuses, the ear, or the skull base. The impact of air travel on individuals with pneumocephalus remains uncertain despite ongoing research. We report a unique case of spontaneous tension pneumocephalus attributed to a frontal sinus osteoma during air travel. Case Presentation: A 55-year-old man presented with headache and dizziness, initiated during a nine-hour international flight two weeks prior. The symptoms abated after landing but recurred on his return flight, accompanied by confusion the following day. A neurological examination revealed no deficits. CT and MRI scans indicated the presence of intraparenchymal air collection in the right frontal lobe, attributed to a frontal sinus osteoma causing a dural tear. Surgical intervention included duroplasty and osteoma removal, with postoperative recovery free of complications. Conclusions: Frontal sinus osteoma-induced tension pneumocephalus is exceedingly rare, with only limited cases reported in the literature. This case shows that air travel may exacerbate intracranial gas dynamics that lead to development of tension pneumocephalus with a potentially fatal outcome for patients.